2018
DOI: 10.1111/imig.12516
|View full text |Cite
|
Sign up to set email alerts
|

Brokering International Education and (re)producing Class in Mumbai

Abstract: This article discusses the role that education brokers play in the decision‐making processes of international students in Mumbai, India. Drawing on 80 interviews with students and education brokers, the analysis reveals how the services that brokers provide, and who accesses them, are shaped by the class status of prospective international students within the localized and granular hierarchies of Mumbai's upper‐middle‐class. Brokers are divided into agents and counsellors, who offer different service models an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 54 publications
0
24
0
Order By: Relevance
“…Education agents have played an important role in bridging HEIs and international students, as well as exerting subtle and lasting influences (Bista, 2017;Dunstan, 2011;Kauppinen et al, 2014;Newcomb, 2017;Raimo, 2013;Raimo et al, 2014;Robinson-Pant & Magyar, 2018;Tian, 2017;Tuxen & Robertson, 2018;Yu, 2016). In Dunstan (2011)'s study of agents in the context of Australia, she noted that agents were an indispensable part of Australian international education since over 60% of international students were recruited through agents.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Education agents have played an important role in bridging HEIs and international students, as well as exerting subtle and lasting influences (Bista, 2017;Dunstan, 2011;Kauppinen et al, 2014;Newcomb, 2017;Raimo, 2013;Raimo et al, 2014;Robinson-Pant & Magyar, 2018;Tian, 2017;Tuxen & Robertson, 2018;Yu, 2016). In Dunstan (2011)'s study of agents in the context of Australia, she noted that agents were an indispensable part of Australian international education since over 60% of international students were recruited through agents.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In one such study, research had been conducted with international office staff and it was found that there was an absence of transparency in the agent-HEI relationship as well as commission arrangements where agents were compensated for their work in recruiting students to a university (Robinson-Pant & Magyar, 2018). Fraudulence was another recurring issue noted in agent practices (Bista, 2017;Kauppinen et al, 2014;Newcomb, 2017;Tuxen & Robertson, 2018;Yu, 2016). Newcomb (2017)'s interview with eight undergraduate admission officers who assessed international students at highly selective HEIs in the United States revealed examples of inaccurate descriptions in applicants' resume, falsified documents, and fraudulence in standardized tests.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to globalisation processes, national state policy initiatives, global marketisation (Findlay et al, 2016) of educational export, new migration stakeholder appear. Previous studies show different aspects of this process: recruiting of international students as skilled migrants (Ziguras and Law, 2006), the role of institutions for study migration (Basford and Riemsdijk, 2017), brokerage industry (Tuxen and Robertson, 2018) highlighting competition of 'world-class universities' (Prazeres et al, 2017) for the "best and brightest" (Findlay et al, 2012) in order to improve their job prospects (Heaviside et al, 2018). Many Western countries are competing to attract a global talent pool.…”
Section: Introductionmentioning
confidence: 99%